Interactive Clinical Avatar Use in Pharmacist Preregistration Training: Design and Review - Thompson, Jessica; White, Simon; Chapman, Stephen (JMIR Publications, 2020)
BackgroundVirtual patients are interactive computer-based simulations that are being increasingly used in modern health care education. They have been identified as tools that can provide experiential learning and assessment in a standardized and safe environment. However, the study of high-fidelity virtual patients such as interactive clinical avatars within pharmacy is limited. ObjectiveThe aim of this paper is to describe the design and review of three interactive clinical avatar simulations as part of pharmacist preregistration training. MethodsA multistep design approach was taken to create interactive clinical avatar simulations on the topics of emergency hormonal contraception (EHC), calculation of renal function, and childhood illnesses. All case studies were reviewed by registered pharmacists to establish content and face validity. The EHC case study and data collection questionnaire were also reviewed by a purposive sample of preregistration trainees and newly qualified pharmacists. The questionnaire used Likert ranking statements and open-ended questions to obtain users' feedback on the design, usability, and usefulness of the interactive clinical avatars as learning tools. Descriptive statistics and content analysis were undertaken on the data. ResultsTen preregistration trainees and newly qualified pharmacists reviewed the EHC interactive clinical avatars and data collection questionnaire. The data collection questionnaire was associated with a Cronbach alpha=.95, demonstrating good reliability. All three interactive clinical avatar simulations were reported as usable and appropriately designed for preregistration training. Users perceived they were developing skills and knowledge from the simulations. The high-fidelity nature of the avatars and relevance of the simulations to real-life practice were reported as aspects that encouraged the application of theory to practice. Improvements were suggested to ensure the simulations were more user-friendly. ConclusionsThe design and creation of the interactive clinical avatar simulations was successful. The multistep review process ensured validity and reliability of the simulations and data collection questionnaire. The in-depth explanation of the design process and provision of a questionnaire may help widen the use and evaluation of interactive clinical avatars or other simulation tools in pharmacy education. The interactive clinical avatars were reported as novel learning tools that promoted experiential learning and allowed users to feel like they were engaging in real-life scenarios, thus developing transferable knowledge and skills. This may be potentially beneficial for many health care training courses as a way to provide standardized experiences promoting active learning and reflection.